Metagenomics reveals divergent functional profiles of soil carbon and nitrogen cycling under long-term addition of chemical and organic fertilizers in the black soil region - Hu, Xiaojing; Gu, Haidong; Liu, Junjie; Wei, Dan; Zhu, Ping; Cui, Xi'an; Zhou, Baoku; Chen, Xueli; Jin, Jian; Liu, Xiaobing; Wang, Guanghua (Geoderma, 2022)
•Biogeographic distance rather than fertilization dominated microbial functional profiles in Mollisols.•Chemical fertilization promoted processes of methane oxidation, soil N degradation, nitrification and anammox.•Manure fertilization shifted C fixation and degradation processes and facilitated nitrate reduction.•Chemical plus manure fertilization could potentially enhance N2O emission via denitrification.•Soil P contents were the most influential factor in controlling microbial functional profiles. The long-term effects of different fertilization regimes on the microbial functional potential of soils involving nutrient cycling remain largely unknown. Here, metagenomic sequencing was applied to investigate the influences of long-term chemical and organic fertilization on soil microbial C and N cycling across southern, middle and northern sites of black soil region in Northeast China. The results showed that biogeographic distance induced the most influential on the microbial functional profiles of soil C and N cycling, and significant effects of manure fertilization were detected across three experimental sites. Organic fertilization enriched the relative abundances of Proteobacteria and Planctomycetes that carry C and N cycling genes, while inhibited the growth of oligotrophic groups such as Verrucomicrobia. Chemical fertilization increased the gene abundances involved in methane oxidation, but had little effect on soil C degradation and fixation. Contrarily, manure fertilization, particularly the combination of chemical and organic fertilizers (CFM), significantly decreased the abundance of cooC (reductive acetyl-CoA pathway) and coxS (CO oxidation) while enhanced the abundance of icd (rTCA cycle), which are involved in C fixation. Additionally, chemical fertilization enriched the gene abundance that involved in soil N degradation, nitrification and anammox, whereas manure fertilization was beneficial for the functional potentials of assimilatory and dissimilatory nitrate reductions across the black soils. However, CFM significantly promoted the soil denitrification potential, possibly due to excess N input, which might result in soil N loss via the emission of nitrogenous gas in this region. Furthermore, the substantial enhancement in soil P contents induced by manure addition predominantly affected the C and N cycling profiles, abundance of functional genes and microbial taxa. Moreover, diverse correlations between C and N cycling genes suggested the synergetic or antagonistic interactions of C and N metabolic potentials in the black soils. Overall, this study provided in-depth insights into distinct microbial functional potentials under long-term chemical and organic fertilization that may have predictable consequences for soil nutrient cycling in agroecosystems of black soil region.